Catering for EAL/D students' language needs in mainstream classes: Early childhood teachers' perspectives and practices in one Australian setting - Dobinson, Toni; Buchori, S. (Social Science Press, 2016)
This article aims to highlight the complexity of English language related experiences and interactions of a small group of teachers in an Australian, Early Childhood (EC), mainstream setting with children four to eight years old. It draws on data collected from a qualitative case study which investigated four teachers' perspectives and anxieties when it comes to 1) achieving a balance between use of home languages and the use of Standard Australian English in classrooms 2) mainstream teacher knowledge of, and confidence in, using appropriate practices to enhance English language learning experiences for EAL/D students in mainstream classes. Through data collected from teachers via semi-structured interviews, and observations of teaching practices, discussion focuses on the challenges and dilemmas that mainstream teachers can face in the absence of effective formalised English language teacher education. Recommendations for possible ways forward are made.